2020
DOI: 10.1039/d0ra03580g
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of green silver nanoparticles against ampicillin-resistant Klebsiella pneumoniae

Abstract: Utilizing novel SNPs synthesized by Nostoc Bahar M sp. to combat the emergence of multidrug-resistant (MDR) strains of this bacterium through targeting virulence and resistance signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…(N-SNPs) was assessed against drug-resistant K. pneumoniae. 124 The results demonstrated for the first time the relationship between biogenic silver-NPs and genes related to a bacterial secretion system. N-SNPs resulted in downregulation of the hns, hcp-1, VgrG-1, and VgrG-3 genes responsible for inducing the secretion system.…”
Section: Antimicrobial Activity Antibacterial Activitymentioning
confidence: 88%
See 3 more Smart Citations
“…(N-SNPs) was assessed against drug-resistant K. pneumoniae. 124 The results demonstrated for the first time the relationship between biogenic silver-NPs and genes related to a bacterial secretion system. N-SNPs resulted in downregulation of the hns, hcp-1, VgrG-1, and VgrG-3 genes responsible for inducing the secretion system.…”
Section: Antimicrobial Activity Antibacterial Activitymentioning
confidence: 88%
“…135 For illustration, the decrease in GSH level after exposure the cells to NPs lead to accumulation of ROS causing oxidative stress. 124 Similarly, the imbalance in antioxidant enzymes such as GPx, 123 superoxide dismutase, catalase, etc., results in oxidative stress causing cellular dysfunction and led to cell death. 136 On the other side, other studies suggested that the direct interaction between NPs and cellular targets (such as mitochondrial respiration, metabolism, inflammation, etc.)…”
Section: Killing Strategies Of Nps Against Living Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silver NPs (SNPs) have unique physicochemical and biological features that make them attractive in various domains, including medicine, agriculture, and industry [ 18 ]. These particles are also a promising alternative therapeutic agents against many diseases, including microbial and viral infections [ 12 , 29 , 30 ] and cancer [ 24 ], and for the treatment of burns [ 31 ]. For example, an SNP-based bandage approved by the Food and Drug Administration as a treatment for burns is already commercially available under the trade name of Acticoat [ 31 ].…”
Section: Introductionmentioning
confidence: 99%